Clinically Feasible Biofilm Susceptibility Assay for Isolates of Pseudomonas aeruginosa from Patients with Cystic Fibrosis - Moskowitz, Samuel M. (American Society for Microbiology, 2004)
Pseudomonas aeruginosa is the predominant cause of chronic airway infection in cystic fibrosis (CF). CF airway isolates are often tested for antibiotic susceptibility but are rarely eradicated by the antibiotics identified as potentially effective. The growth state of P. aeruginosa in CF airways is probably different from that exhibited under conventional susceptibility testing conditions and may represent a bacterial biofilm. Biofilm susceptibility testing methods were adapted to create an assay for implementation in a clinical microbiology laboratory. This assay gave reproducible results when examined in 300 paired determinations with 12 antimicrobial agents, with a serious error rate of 5.7%. The biofilm assay was used retrospectively to test these 12 agents against 94 isolates from 41 CF patients. The biofilm inhibitory concentrations (BICs) were much higher than the corresponding conventionally determined MICs for the β-lactam antibiotics (median values: aztreonam, >128 μg/ml versus 4 μg/ml; ceftazidime, 128 μg/ml versus 2 μg/ml; piperacillin-tazobactam, 256 μg/ml versus 4 μg/ml; and ticarcillin-clavulanate, 512 μg/ml versus 16 μg/ml, respectively) and doxycycline (>64 μg/ml versus 16 μg/ml); and similar for meropenem (4 μg/ml versus ≤ 1 μg/ml), ciprofloxacin (0.5 μg/ml versus 1 μg/ml), and the aminoglycosides amikacin (32 μg/ml versus 16 μg/ml), gentamicin (16 μg/ml versus 8 μg/ml), and tobramycin (4 μg/ml versus 2 μg/ml). The median BIC for azithromycin was 2 μg/ml, whereas isolates were uniformly resistant when tested by standard methods. This demonstrates the feasibility of adapting biofilm susceptibility methods to the clinical microbiology laboratory and opens the way to examining whether biofilm testing might be used to select more effective antibiotic combinations for CF airway infections than methods in current use.